2020
DOI: 10.1021/acs.orglett.0c02801
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Hexahydroimidazo[1,2-a]quinolines via SN2-Type Ring-Opening Hydroarylation–Hydroamination Cascade Cyclization of Activated Aziridines with N-Propargylanilines

Abstract: A novel synthetic approach for the construction of 1,2,3,3a,4,5-hexahydroimidazo­[1,2-a]­quinolines in good yields (up to 75%) with excellent stereoselectivity (dr up to 94:6, ee up to >99%) under one-pot domino ring-opening cyclization (DROC) conditions has been developed. The DROC protocol proceeds through a Lewis acid catalyzed SN2-type ring-opening of activated aziridines with N-propargylanilines followed by intramolecular cyclization comprising concomitant hydroarylation and hydroamination steps in a domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…70 The functionalization of C(sp 3 )-H bonds of azirine molecules 71 are challenging due to high ring strain and facile ring-opening reactions. 72 Majee and coworkers developed a method for acyloxylation of 2H-azirine molecules using PhI(OAc)2 or PIDA as acyl source under visible light irradiation using organo-photocatalyst (Figure 10). 73 In this study, they concluded that 2 mol % of Rose Bengal (RB) as photocatalyst was good enough for the C(sp 3 )-H acyloxylation of 3-aryl-2H-azirines 26 using 2 equiv of PIDA under blue LED irradiation.…”
Section: Figurementioning
confidence: 99%
“…70 The functionalization of C(sp 3 )-H bonds of azirine molecules 71 are challenging due to high ring strain and facile ring-opening reactions. 72 Majee and coworkers developed a method for acyloxylation of 2H-azirine molecules using PhI(OAc)2 or PIDA as acyl source under visible light irradiation using organo-photocatalyst (Figure 10). 73 In this study, they concluded that 2 mol % of Rose Bengal (RB) as photocatalyst was good enough for the C(sp 3 )-H acyloxylation of 3-aryl-2H-azirines 26 using 2 equiv of PIDA under blue LED irradiation.…”
Section: Figurementioning
confidence: 99%
“…There are only two reported strategies for the general synthesis of imidazoquinolines [10–11] . Ghorai and co‐workers have accomplished a Lewis acid‐catalyzed ring‐expansion with activated aziridines and N ‐propargylaniline for the assembly of imidazoquinoline derivatives [10] . Kutateladze et al have developed a series of straightforward photoassisted reaction systems allowing access to polyheterocyclic molecular architectures [11] .…”
Section: Figurementioning
confidence: 99%
“…However, the synthesis of imidazoquinolines is a much less explored research field. There are only two reported strategies for the general synthesis of imidazoquinolines [10–11] . Ghorai and co‐workers have accomplished a Lewis acid‐catalyzed ring‐expansion with activated aziridines and N ‐propargylaniline for the assembly of imidazoquinoline derivatives [10] .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations